Prevalence and Multisystemic Health Manifestations of Arsenicosis in Krishnanagar Union, Brahmanbaria District, Bangladesh (Journal of Bio-Science, 2026)
Arsenic contamination in drinking water is a major environmental and public health concern in Bangladesh and is responsible for chronic multisystemic illness known as arsenicosis. This study was conducted in Krishnanagar union of Nabinagar Upazila, Brahmanbaria District- one of the most arsenic-prone areas- to assess the extent of arsenic exposure and its associated health complications. Data were collected under the UNICEF Bangladesh–funded arsenic mitigation project Lot 2, implemented by Village Education Resource Center (VERC), through communitybased participatory rural appraisal (PRA) techniques and door-to-door household visits. Among 6,864 families surveyed, 1,953 were consuming arsenic-contaminated water, 3,217 relied on untested tube wells, and only 1,694 used wells within acceptable limits. Of the tested wells, 47% contained arsenic above 50 ppb (unsafe), 32% were within the WHO guideline (≤10 ppb) as safe and 21% were within the national permissible limit (≤50 ppb), while 46% remained untested. Clinical observation identified 129 individuals with dermatological and systemic manifestations, of whom 56 were clinically confirmed as arsenicosis cases. Among the confirmed cases, the predominant manifestations included melanosis and leukomelanosis (62.5%), palmoplantar keratosis (76.8%), ulcerated keratosis (64.3%), conjunctivitis (42.9%), gangrene (12.9%), mees’ lines (3.6%), peripheral neuropathy (83.9%), fatigue (89.3%), odynophagia (26.8%), chronic cough and dyspnea (32.1%), dental caries (39.3%), chronic abdominal pain (8.9%), anorexia and nausea (23.2%), altered bowel habits (5.4%), and alopecia (32.1%). Spearman’s correlation showed no significant link between exposure duration and symptom severity (ρ=0.038, p=0.779), suggesting that biological susceptibility or arsenic concentration may be more decisive than exposure length alone. These results highlight a significant multisystemic health burden within the study area, necessitating urgent safe water access, increased awareness, and targeted health interventions.J. Bio-Sci. 34(1): 100-109, 2026